Answer:
11
Step-by-step explanation:
When we multiply the polynomials we will get:
(5x^2+2x)(3x^2-7x+4)
=5x^2(3x^2-7x+4)+2x(3x^2-7x+4)
=15x^4-35x^3+20x^2+6x^3-14x^2+8x
=15x^4+(6x^3-35x^3)+(20x^2-14x^2)+8x
=15x^4-29x^3+6x^2+8x
The correct answer is C
Answer:
2/6
Step-by-step explanation:
Ok, so if the fraction is 1/3 and the denominator needs to be 6, then what you do is figure out what would turn 3 into 6. So, 3 x 2 would equal 6 and then you would have to also keep that two and multiply that 2 with the 1 and you would get 2. That would lead to the numerator being 2 and the denominator being 6, or 2/6.
Answer:
Y=3x+3
Step-by-step explanation: